Placenta Creta: A Spectrum of Lesions Associated with Shallow Placental Implantation - Jerzy Stanek (Obstetrics and Gynecology International)
Background. On placental histology, placenta creta (PC) ranges from clinical placenta percreta through placenta increta and accreta (clinical and occult) to myometrial fibers with intervening decidua. This retrospective study aimed to investigate the clinicopathologic correlations of these lesions. Methods. A total of 169 recent consecutive cases with PC (group 1) were compared with 1661 cases without PC examined during the same period (group 2). The frequencies of 25 independent clinical and 40 placental phenotypes were statistically compared between the groups using chi-square test or analysis of variance where appropriate. Results. Group 1 placentas, as compared with group 2 placentas, were statistically significantly (p<0.05) associated with caesarean sections (11.2% vs. 7.5%), antepartum hemorrhage (17.7% vs 11.6.%), gestational hypertension (11.2% vs 4.3%), preeclampsia (11.8% vs 2.6%), complicated third stage of labor (18.9% vs 6.4%), villous infarction (14.2% vs 8.9%), chronic hypoxic patterns of placental injury, particularly the uterine pattern (14.8%, vs 9.6%), massive perivillous fibrin deposition (9.5% vs 5.3%), chorionic disc chorionic microcysts (21.9% vs 15.9%), clusters of maternal floor multinucleate trophoblasts (27.8% vs 21.2%), excessive trophoblasts of chorionic disc (24.3% vs 17.3%), segmental fetal vascular malperfusion (27.8% vs 19.9%), and fetal vascular ectasia (26.2% vs 15.2%). Conclusion. Because of the association of PC with gestational hypertensive diseases, acute and chronic placental hypoxic lesions, increased extravillous trophoblasts in the chorionic disc, chorionic microcysts, and maternal floor trophoblastic giant cells, PC should be regarded as a lesion of abnormal placental implantation and abnormal trophoblast invasion rather than decidual deficiency only.